REGIONALISM AS THE IDENTITY OF ECO-AIRPORT: DEVELOPMENT OF NUSAWIRU AIRPORT PANGANDARAN - Andiani, Nathania
Nowadays, air transportation is one type of transportation that is very important for human mobility. It is caused by air transportation is an effective, efficient, fast, safe, and comfortable transportation. The reasons people using air transportation service include business interests, tourism, and various other matters. Nusawiru Airport is a domestic airport located in Pangandaran City, West Java. The development of this passenger terminal will replace the old Terminal which will be converted into an Indonesian Aviation School. Pangandaran has a lot of tourism potential and the government will improve air transportation facilities to increase the number of tourists who come to Pangandaran. To increase the tourism potential, Nusawiru airport will be developed referring to KM (Ministerial Decree) 407 of 2014, passenger area will increase to 3500 m² and 3000 m² of parking area. It can accommodate 128 passengers during peak hours or 250,000 people per year. Limited area and efficiency in further development, this airport configuration uses the concept of a linear form with a 1.5-storey system. As a result, airport is one of the gateways to the identity of a city. However, the issue of airport development has become a concern for every country in the world. An airport as a gateway and symbol of a city, region, and country makes the government compete to build airports with the latest technological designs without looking at the surrounding context and even eliminating the identity of a city. Another concern is issue of the enormous energy use of an airport's activities. Therefore, the design of Nusawiru Airport will take the concept of Regionalism Architecture. This airport will warmly welcome the visitors with elements of locality that are integrated with contemporary style. The green airport (eco-airport) concept is also applied to efficient use of energy in buildings by maximizing natural lighting and ventilation, using renewable energy, reuse of wastewater, and waste management.